2019
DOI: 10.1016/j.aucc.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Structures, processes and outcomes of specialist critical care nurse education: An integrative review

Abstract: Objectives: To review and synthesise international literature to reveal the contemporary structures, processes and outcomes of critical care nurse (CCN) education. Method: An integrative review on specialist critical care education was guided by Whittemore and Knafl's integrative review steps: problem-identification; literature search; and data evaluation, analysis and presentation. Donabedian's Quality Framework (Structure-Process-Outcome) provided a useful analytical lens and structure for the reporting of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The provision of high-quality critical care education has many aspects and complex problems. Health education and education providers must prepare the best practice structures and processes for training critical care specialists who meet the needs of the organization (Gullick et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The provision of high-quality critical care education has many aspects and complex problems. Health education and education providers must prepare the best practice structures and processes for training critical care specialists who meet the needs of the organization (Gullick et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The survey also highlighted that lack of recognition for critical care as a speciality and lack of protection for the title, also impacted education programs (Endacott et al, 2015). More recently a review of specialist critical care nurse education identified the importance of collaborative education provision between clinical settings and recognised education providers, and for structures, outcomes and unit, organisational, and governmental policy to align with future expectations and current and emerging need (Gullick et al, 2019).…”
Section: Editorialmentioning
confidence: 99%
“…Transfer of specialty postgraduate nursing education from hospitals to higher education began in the early to late 1990s. Even in specialty education, international variations exist (Marshall 2019) in addition to questions about poorly reported practice and patient impacts of postgraduate education (Gullick et al 2019;Ng et al 2014). Most post-registration education in critical care existed as ad-hoc training for nurses and doctors together until the 1960s, when more formalized post-registration education was developed in Australia and the UK (Marshall 2019).…”
Section: Emergence Of Specialty Educationmentioning
confidence: 99%
“…Most post-registration education in critical care existed as ad-hoc training for nurses and doctors together until the 1960s, when more formalized post-registration education was developed in Australia and the UK (Marshall 2019). In some settings today, hospitals and health services offer specialist nurse education as part of partnership arrangements with tertiary institutions (Gullick et al 2019).…”
Section: Emergence Of Specialty Educationmentioning
confidence: 99%